PENERIMAAN WAGYU SEBAGAI SHOKU BUNKA JEPANG DI INDONESIA - Ratna, Maharani Patria (Faculty of Humanities, Diponegoro University, 2017)
(Title: Wagyu Reception As A Shoku Bunka in Indonesia) Wagyu is popular for its quality and its delicious taste. Nowadays wagyu has became a trademark for the best quality of beef. Wagyu is originally from Japan that now has spread to all over the world. 13 years ago, Indonesian government has banned the import of wagyu. But now the ban has been revoked. As a result some of indonesian people are still not familiar with the term of â€œwagyuâ€. The purpose of this study are to know whether wagyu has been received as one of Japanese food or not and also the reasons behind it. This study is done by searching some references from trusted sources to answer those questions. The results of this study are wagyu has been well received by the people of Indonesia. The reasons are wagyu is already certified as halal food by MUI, now that in Indonesia there are many local breedres that produce local wagyu, and also recently there are many Indonesian food recipes that uses wagyu as its main ingredient.